General Quadratic-Additive Type Functional Equation and Its Stability - Yang-Hi Lee; Soon-Mo Jung (International Journal of Mathematics and Mathematical Sciences)
We investigate the general functional equation of the form f(ax+by+cz)-abf(x+y)-bcf(y+z) − acf(x+z)-a((a+1)/2-b-c)f(x)-b((b+1)/2-a-c)f(y)-c((c+1)/2-a-b)f(z)-(a(a-1)/2)f(-x) − (b(b-1)/2)f(-y)-(c(c-1)/2)f(-z)=0, whose solutions are quadratic-additive mappings in connection with stability problems.